Effects of Motivation on English Language Proficiency of The ESL Learners - Muhammad Tanveer Aslam,; Tanweer, Lubna (JELLL, 2025)
The purpose of this study was to find out the effect of motivation on the English language proficiency of ESL learners at the secondary school level. The study aimed to investigate the learners’ and teachers’ views on the effect and role of motivation on the English language proficiency of ESL learners. Two research objectives were made for this research. The mixed method research was used for this study and two stage sampling technique (Purposive, convenient) were used to select the sample of 400 students for questionnaire data and 6 English teachers for interview from public and private schools of Karachi. The tools for this research were semi-structured interviews and questionnaire. The questionnaire comprised on 24 close-ended statements that were developed on 5 points Likert type scale. The reliability of the instrument was found at 0.864. The interview protocol comprised on 12 questions related to research objectives. The data were analyzed by using two techniques thematic analysis and descriptive statistical techniques. To find out the difference between gender wise t-test was applied. Based on the findings of the research, the result indicated that there is a great effect of motivation on English language learners. So, it is concluded that motivation is an influential factor in learning activity. Without motivation, goals of learning are hard to be achieved because the students’ effort and desire affect the learners in achieving the learning goals. Keywords: Effect, role, motivation, language, proficiency, learners.